1997
DOI: 10.1080/136588197242158
|View full text |Cite
|
Sign up to set email alerts
|

Mapping urban air pollution using GIS: a regression-based approach

Abstract: As part of the EU-funded SAVIAH project, a regression-based methodology for mapping tra c-related air pollution was developed within a GIS environment. Mapping was carried out for NO2 in Amsterdam, Hudders® eld and Prague. In each centre, surveys of NO2 , as a marker for tra c-related pollution, were conducted using passive di usion tubes, exposed for four 2-week periods. A GIS was also established, containing data on monitored air pollution levels, road network, tra c volume, land cover, altitude and other, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
330
1
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 564 publications
(345 citation statements)
references
References 33 publications
(29 reference statements)
8
330
1
6
Order By: Relevance
“…First developed by Briggs et al (1997), LUR has been proved to have more advantages than other conventional approaches (Hoek et al 2008). By means of establishing a statistical relationship between pollutant concentrations measured at 20-100 sites and potential influencing factors such as land use, traffic, and population density, LUR is able to predict concentrations at unsampled locations throughout a given domain within the framework of GIS (Henderson et al 2007;Hoek et al 2008).…”
Section: Responsible Editor: Gerhard Lammelmentioning
confidence: 99%
“…First developed by Briggs et al (1997), LUR has been proved to have more advantages than other conventional approaches (Hoek et al 2008). By means of establishing a statistical relationship between pollutant concentrations measured at 20-100 sites and potential influencing factors such as land use, traffic, and population density, LUR is able to predict concentrations at unsampled locations throughout a given domain within the framework of GIS (Henderson et al 2007;Hoek et al 2008).…”
Section: Responsible Editor: Gerhard Lammelmentioning
confidence: 99%
“…Because NO 2 concentrations vary on a fine spatial scale, direct interpolation will result in systematic prediction errors related to emission sources in the area ( Stedman et al, 1997 ). On a smaller spatial scale, the SAVIAH study has found that regression -based methods using external information, such as distance to major roads, were superior to interpolation methods in explaining within-city variation of NO 2 concentrations (Briggs et al, 1997 ). In a UK study (Stedman et al, 1997 ), the percentage of urban and suburban land cover at two spatial scales ( 100 and 25 km 2 around the sites) and estimated emission from major road vehicle sources in an area of 4 km 2 around the site were used as predictors in a regression model for NO 2 .…”
Section: Urban Backgroundmentioning
confidence: 99%
“…In the SAVIAH study, individual exposure estimates for study subjects were generated based on concentration measurements at a limited number of sites and prediction of these concentrations using data on explanatory variables available in a GIS ( Briggs et al, 1997 ). Regression models were developed using factors such as traffic intensity near the sites, distance to major roads, population density, and sampling height to explain the measured concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lieu of using home-specific outdoor measurements to determine ambient-generated pollutant exposures (which would be nearly as labor-intensive as indoor monitoring), factors generated from Geographic Information Systems (GIS), such as distance from road, population density, and land use can be used in combination with central site monitoring data to estimate ambient exposures (Briggs et al 1997;Brauer et al 2003). Questionnaire (e.g., opening of windows, air conditioning usage) and/or property assessment data on individual building characteristics can then be used to estimate residential ventilation patterns (Long et al 2001;Setton et al 2005) that potentially affect the influence of ambient concentrations and indoor sources (Abt et al 2000).…”
Section: Introductionmentioning
confidence: 99%